Preinfarction Angina and Improved Reperfusion of the Infarct-related Artery - Andreotti, Felicita; Sciahbasi, Alessandro; De Marco, Eugenia; Maseri, Attilio (Thrombosis and Haemostasis, 1999)
Preinfarction angina and early reperfusion of the infarct-related artery are major determinants of reduced infarct-size in patients with acute myocardial infarction. The beneficial effects of preinfarction angina on infarct size have been attributed to the development of collateral vessels and/or to post-ischemic myocardial protection. However, recently, a relation has been found between prodromal angina, faster coronary recanalization, and smaller infarcts in patients treated with rt-PA: those with preinfarction angina showed earlier reperfusion (p = 0.006) and a 50% reduction of CKMB-estimated infarct-size (p = 0.009) compared to patients without preinfarction angina. This intriguing observation is consistent with a subsequent observation of higher coronary recanalization rates following thrombolysis in patients with prodromal preinfarction angina compared to patients without antecedent angina. Recent findings in dogs show an enhanced spontaneous lysis of plateletrich coronary thrombi with ischemic preconditioning, which is prevented by adenosine blockade, suggesting an antithrom-botic effect of ischemic metabolites. Understanding the mechanisms responsible for earlier and enhanced coronary recanalization in patients with preinfarction angina may open the way to new reperfusion strategies.A vast number of studies, globally involving ≈17,000 patients with acute myocardial infarction, have unequivocally shown that an infarction preceded by angina evolves into a smaller area of necrosis compared to an infarct not preceded by angina (Table 1) (1). So far, preinfarction angina has been thought to have cardioprotective effects mainly through two mechanisms: collateral perfusion of the infarctzone (2-4), and ischemic preconditioning of the myocardium (5-7). Here we discuss a further mechanism of protection represented by improved reperfusion of the infarct-related artery.
Keywords: Prodromal angina; myocardial infarction; reperfusion; thrombolysis